Physicochemical Properties of Nanoliposomes Encapsulating Grape Seed Tannins Formed with Ultrasound Cycles - Osorio-Lira, F; Monasterio-Aranda, A (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Grape seeds are an excellent source of flavonoids and tannins with powerful antioxidant properties. However, the astringency of tannins limits their direct incorporation into food. To overcome this challenge, we investigated the encapsulation of grape seed tannins within nanoliposomes formed by ultrasound cycling. We characterized the nanoliposomes’ physicochemical properties, including encapsulation efficiency, antioxidant activity, stability, microstructure, and rheological properties. Our findings reveal that the nanoliposomes exhibited excellent stability under refrigerated conditions for up to 90 days with a mean particle size of 228 ± 26 nm, a polydispersity index of 0.598 ± 0.087, and a zeta potential of −41.6 ± 1.30 mV, maintaining a spherical multilamellar microstructure. Moreover, they displayed high antioxidant activity, with encapsulation efficiencies of 79% for epicatechin and 90% for catechin. This innovative approach demonstrates the potential of using ultrasound-assisted nanoliposome encapsulation to directly incorporate grape seed tannins into food matrices, providing a sustainable and efficient method for enhancing their bioavailability and functionality. © 2024 by the authors.